THE ALLELOPATHIC CONNECTIONS OF SPIROCHETES LEPTOSPIRAINTERROGANS IN PHYTOCOENOSISES OF MARSHY MEADOWS - Гулай, В. В. (Scientific Progress & Innovations, 2013)
There is information on the environmental characteristics of the relationship of higher plants and pathogenic leptospirs in plant communities marshy meadows Forest-Steppe zone of Ukraine. The basis of the environmental impact of these representatives vegetation habitats for spirochetes are topical type of biotic linkages, resulting in the allocation of water-soluble substances allelopathy activity as living plants and their residues. In general, background vegetation types show a negative effect on the pathogen leptospirosis, which reduces the time spent in these spirochetes phytocenoses marshy meadows.